ANALISIS KESESUAIAN LANGKAH-LANGKAH PEMBELAJARAN PADA RENCANA PELAKSANAAN PEMBELAJARAN GURU MATA PELAJARAN BIOLOGI DENGAN PENDEKATAN SAINTIFIK DI SMA YANG TELAH MENERAPKAN KURIKULUM 2013 - Widya Utami; Djunaidah Zen; Kodri Madang (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2015)
Abstract: This research aims to find out the level of conformity measures study on RPP teacher of Biology and completeness of components form composing RPP teacher Biology class X in the top 3 of high school in Palembang. A method used is descriptive method. The data was done in the top 3 of high school with the subject of the research three teacher Biology class X in the top 3 of high school in Palembang. Based on the results of the analysis that has been done, the level of confirmity of RPP substance are in the category of very appropriate, appropriate, and very appropriate.This incompatibility is a substance measures the study on core activities not suitable with the five aspects of the scientific approach (5M) that is set in Kemendikbud 2013. The confirmity level of completeness of RPP components are in the category of very fit. RPP Components in the category of very fit is the identity of the subjects, core competency, basic competency, indicator of attaintment of competency, the purpose of the study, study material, and source of study. Components that are in a suitable category is scenario of learning and assessment Keywords : Learning Plan, Scientific Approach, Biology